1974
DOI: 10.3382/ps.0532082
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Increased Hatchability at High Altitude

Abstract: A line of medium white turkeys developed at an altitude of 105 meters above sea level was reproduced and reared at 1524 meters above sea level for seven generations. One half of the population was selected for seven generations for increased hatchability based on individual hen performance. The other half of the population was selected at random each year. Records were kept of percent hatchability, percent fertility, average number of eggs set, average egg weight, body weight at two, eight, and 20 weeks of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1976
1976
1994
1994

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Ells and Morris (1947), Meshew (1949), and Stephenson (1950) reported on the effects of adding supplemental oxygen during the incubation period. Cramer et al (1974) reported on results of selecting for hatchability at an elevation of 1524 meters. In addition to reporting on the improvement in hatchability of fertile eggs (HFE) resulting from selection, Cramer et al (1974) reported that the selection procedure had no adverse effects upon mature body weight and body conformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ells and Morris (1947), Meshew (1949), and Stephenson (1950) reported on the effects of adding supplemental oxygen during the incubation period. Cramer et al (1974) reported on results of selecting for hatchability at an elevation of 1524 meters. In addition to reporting on the improvement in hatchability of fertile eggs (HFE) resulting from selection, Cramer et al (1974) reported that the selection procedure had no adverse effects upon mature body weight and body conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Cramer et al (1974) reported on results of selecting for hatchability at an elevation of 1524 meters. In addition to reporting on the improvement in hatchability of fertile eggs (HFE) resulting from selection, Cramer et al (1974) reported that the selection procedure had no adverse effects upon mature body weight and body conformation. Moore and Price (1948) reported on the effects of altitude stressing upon body weights and the weights of organs of reproduction in various mammalian species.…”
Section: Introductionmentioning
confidence: 99%